2013
DOI: 10.1037/a0029138
|View full text |Cite
|
Sign up to set email alerts
|

Internal structure of the Reflective Functioning Scale.

Abstract: The Reflective Functioning Scale (RFS) was developed to assess individual differences in the ability to mentalize attachment relationships. The RFS assesses mentalization from transcripts of the Adult Attachment Interview (AAI). A global score is given by trained coders on an 11-point scale ranging from antireflective to exceptionally reflective. Coding procedures rely on a distinction of demand and permit questions during the AAI. Demand questions directly probe for reflective functioning (RF), whereas permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 35 publications
7
84
1
3
Order By: Relevance
“…Although the instruments we used are evaluated as high-quality, studies have suggested that the results of self-­report measures and expert ratings may differ [59, 60]. Future research should consider this fact and verify our results by using interview measures, such as the Adult Attachment Interview [61], and expert ratings, such as the Reflective Functioning Scale [25]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the instruments we used are evaluated as high-quality, studies have suggested that the results of self-­report measures and expert ratings may differ [59, 60]. Future research should consider this fact and verify our results by using interview measures, such as the Adult Attachment Interview [61], and expert ratings, such as the Reflective Functioning Scale [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Later on, several researchers examined the link between the two concepts in more detail. The results demonstrated that the development of mentalization is influenced by attachment and attachment figures [24, 25]. In addition, several studies have revealed that a lack of mentalization is closely linked to different types of mental disorders, particularly those that involve pathology of the self, such as borderline personality disorder [24, 26].…”
Section: Introductionmentioning
confidence: 99%
“…The SRF interview has only been used a few times and needs to be better validated. The clinical impression is favorable, but psychometric assessment is needed (Rutiman & Meehan, 2012;Taubner et al, 2012). For the OCD-specific RF interview, there is no rating manual.…”
Section: Limitationsmentioning
confidence: 99%
“…Rudden et al (2008) used a limited number of AAI questions, primarily the demand questions, to create an interview specifically aimed at measuring RF. This interview has been used in a few studies (Rutiman & Meehan, 2012;Taubner et al, 2012). Falkenström et al (in press) used an interview with the first 10 AAI questions for the same purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Asimismo, se tuvo en consideración que, para el caso de la AAI, las preguntas de demanda están determinadas por la guía semi-estructurada diseñada para su realización (Taubner et al, 2012).…”
Section: Instrumentosunclassified